Impact of Weekly Physical Activity on Stress Response: An Experimental Study - de la Vega, Ricardo; Jiménez-Castuera, Ruth; Leyton-Román, Marta (Frontiers in Psychology, 2021)
The aim of this research is focused on analyzing the alteration of the psychophysiological and cognitive response to an objective computerized stress test (Determination Test -DT-, Vienna test SystemÒ), when the behavioral response is controlled. The sample used was sports science students (N = 22), with a mean age of 22.82 (Mage = 22.82; SDyears = 3.67; MPhysicalActivity hours/Week = 7.77; SDhours/week = 3.32) A quasi-experimental design was used in which the response of each participant to the DT test was evaluated. The variable "number of hours of physical activity per week" and the variable "level of behavioral response to stress" were controlled. Before and after this test, the following parameters were measured: activation and central fatigue (Critical Flicker Fusion Threshold (CFF Critical flicker fusion ascending and Critical flicker fusion descending; DC potential), and perceived exertion (Central Rating of Perceived Exertion and Peripheral Rating of Perceived Exertion). Significant differences were found in all of the measures indicated. The usefulness of this protocol and the measures used to analyze the stress response capacity of the study subjects are discussed.